Diethyl pyrocarbonate can detect a modified DNA structure induced by the binding of quinoxaline antibiotics. - Portugal, J (1988)
The reactivity of the 160 bp tyrT DNA fragment towards diethyl pyrocarbonate (DEPC) has been investigated in the presence of bis-intercalating quinoxaline antibiotics and the synthetic depsipeptide TANDEM. At moderate concentrations of each ligand, specific purine residues (mainly adenosines) exhibit enhanced reactivity towards the probe, and several sites of enhancement appear to be related to the sequence selectivity of drug binding. Further experiments were performed with echinomycin at pH 5.5 and 4.6 to facilitate the protonation of cytosine required for formation of Hoogsteen GC base pairs. No significant increase in reactivity was observed under these conditions. Additionally, no protection of deoxyguanosine residues from methylation by dimethyl sulphate was observed in the presence of echinomycin. We conclude that the structural anomaly giving rise to drug-dependent enhanced DEPC reaction is not simply the formation of Hoogsteen base pairs adjacent to antibiotic binding sites. Nor is it due to a general unwinding of the double helix, since we show that conditions which are supposed to unwind the helix lead to a uniform increase in purine reactivity, regardless of the surrounding nucleotide sequence.